(untitled) (SAARC Journal of Agriculture, 2026)
Coastal areas of Bangladesh face significant agricultural challenges due to saline soils, nutrient deficiencies, and environmental stressors, particularly during the late growing season. This study evaluates the comparative effects of biochar application on the growth and yield of cauliflower (Brassica oleracea var. botrytis) and broccoli (Brassica oleracea var. italica) under these conditions. Biochar, a carbon-rich soil amendment, has been shown to improve soil fertility, water retention, and decrease soil salinity, making it a promising solution for sustainable crop production. The study examined the impact of biochar amendment at four rates (2, 4, 6 and 8 tons/ha) on key growth parameters, including plant height, leaf size, curd weight, and yield. Results revealed that while biochar significantly improved growth metrics across both crops, cauliflower demonstrated a more pronounced response in terms of yield and curd weight. Early-stage growth (15 days) showed improvements in leaf number, while leaf size and curd weight benefits persisted throughout the season. Interaction effects between crop type and biochar amendment were crop-specific, highlighting the need for tailored application strategies. This research underscores biochar’s potential to enhance late-season growth and yield in coastal regions, offering critical insights for optimizing agricultural practices in resource-constrained environments. SAARC J. Agric., 23(2): 75-91 (2025)